Evaluation of Vulnerability of the Underground Aquifer of the Gharb Plain with the Help of Gis and Drastic Method (Nw of Morocco) - Nezha, El Mahmouhi; Mohamed, El Wartiti; Rajae, Azelmad; Ridouane, Sadki; Sanae, Berred (European Scientific Journal, ESJ, 2016)
Water is a rare resource and badly distributed in Morocco. In spite of the sectorial politics enterprise by persons responsible during more than 50 years in order to control these resources, the problem of the rarity and the deterioration of the water quality always imposes itself. The aquifer complex of the Gharb constitutes an exceptional water reserve for Morocco but these resources are threatened by different types of pollution (agricultural, urban and industrial) according to the economic progress and the relatively fast demographic growth. In this sense and for a better management and the safeguard of water resources of the deep aquifer of the Gharb that we elaborated a map of vulnerability with the help of the DRASTIC method based on seven parameters, controlling water pollution process, seize under shape of data base managed by a Geographic Information System (GIS). The obtained vulnerability map constitutes an easily usable tool for the identification of risk zones where protection measures are necessary, for a better management of the important water resources of the region and also for the immediate intervention in case of accidental pollution.